Impact of Krushik Agricultural Exhibition on Technology Dissemination and Farmers - , Dheeraj Shinde; , P. A. Patil; , S. S. Godase; , S. V. Karanje; , M. A. Jadhav (Archives of Current Research International, 2024)
Disseminating knowledge and information within the farming community in a short period is a difficult task in developing countries. In the present era, social media may mislead the farming community, resulting in heavy losses. So, agricultural exhibitions based on the principles of ‘Seeing is believing’ & ‘Learning by doing’ must be planned to provide a real site of state-of-the-art advanced technologies developed by different agencies. So, the present study was conducted to analyze the impact of the Live Agricultural Expo, i.e. Krushik-2024, to get information regarding the behaviour and feedback of farmers visiting the Exhibition. The study reveals that the interest of young generation agricultural students is increasing in the agriculture sector. Moreover, live demonstration exhibitions/ farmer’s fairs/ technological weeks like “Krushik” can play a crucial role in the development of the farming community. It has emerged as an excellent platform through which advanced technologies from both public and private sectors can effectively disseminate within a short period.